Verbal working memory and the phonological buffer: The question of serial order. (March 2019) - Majerus, Steve
Abstract: The concept of modality specific buffers for the temporary storage of information is a fundamental characteristic of the Working memory model proposed by Baddeley and Hitch (1974). The phonological input buffer does not make an explicit distinction between the identity and the serial order of memoranda, both relying on phonological codes. This review provides a critical examination of the codes and processes involved in item and serial order maintenance capabilities. On the one hand, an increasing number of studies indicate that brain injury can lead to selective impairment for the short-term retention of item versus serial order information. Neuroimaging studies also reveal the involvement of distinct neural substrates for the retention of item and serial order information, and possibly shared neural substrates for the retention of serial order information in verbal and visuo-spatial modalities. Other studies suggest that phonological processing areas within the dorsal language pathway can store both item and serial order information but via separate representational mechanisms. Overall evidence indicates that serial order information in verbal WM may be represented via multiple processes simultaneously, some being domain general and some being phonological. The phonological serial order codes appear to rely on a dorsal language pathway that has also been proposed to support a phonological buffer system, but even at this level, distinct processes for the coding item and serial order information need to be considered.